ASSESSMENT OF RADIATION DOSE OF MOBILE COMPUTED TOMOGRAPHY IN INTENSIVE CARE UNITS. Issue 1 (2nd September 2021) - Kim, Eunhye; Choi, Yoonseok; Park, Hyemin; Na, Chanyoung; Kim, Jungmin; Kim, Jungsu; Han, Taeho
Abstract: Intra-hospital transport is associated with fatal risks for the occupants of an intensive care unit (ICU). Thus, mobile CT is used in ICUs. In this study, two-dimensional equivalent dose distribution data were expanded using the inverse square law of distance to identify the potential exposure of radiologic technologists and public and the maximum number of possible daily CT procedures. The exposure dose at 1.5 m from the isocentre of the mobile CT was 2.260 μSv. Based on the dose limitation (5 mSv/yr for controlled area and 1 mSv/yr for uncontrolled area) as per National Council on Radiation Protection and Measurement report, the number of possible scans per day was 9 for radiologic technologists and 2 for public. When using the radiation shielding partition with a lead equivalent of 0.3 mmPb, the exposure dose reduced as 0.399 μSv. Therefore, mobile CT can be used in ICUs when appropriate shielding is provided.